Development a low-cost carbon monoxide sensor using homemade CW-DFB QCL and board-level electronics. (May 2018) - Dang, Jingmin; Yu, Haiye; Zheng, Chuantao; Wang, Lijun; Sui, Yuanyuan; Wang, Yiding
Highlights: A 4.7 μm CW-DFB QCL with low threshold current density is realized. A board-level modulation function based laser controller is developed. A board-level analog orthogonal vector lock-in amplifier is developed. The sensor performance has a great improvement compared with our previous work. Abstract: A mid-infrared sensor was demonstrated for the detection of carbon monoxide (CO) at trace level. In order to reduce cost, a homemade continuous-wave mode distributed feedback quantum cascade laser (CW-DFB QCL), a mini gas cell with 1.6-m optical length, and some self-development electronic modules were adopted as excitation source, absorption pool, and signal controlling and processing tool, respectively. Wavelength modulation spectroscopy (WMS) and phase sensitive detection (PSD) techniques as well as wavelet filtering software algorithm were used to reduce the influence of light source fluctuation and system noise and to improve measurement precision and sensitivity. Under the selected P(11) absorption line located at 2099.083 cm −1, a limit of detection (LoD) of 26 parts per billion by volume (ppbv) at atmospheric pressure was achieved with a 1-s acquisition time. Allan deviation was used to characterize the long-term performance of the CO sensor, and a measurement precision of ∼3.4 ppbv was observed with an optimal integration time of ∼114 s. As a field measurement, a continuous monitoring on indoor CO concentration for a period of 24 h was conducted, which verified the reliable and robust operation of the developed sensor.